Clinical study of the role of Procalcitonin and some biochemical parameters in patients with Lymphoma in Thi-Qar Province - Iraq - Hadeel Rashid Faraj (Babcock University Medical Journal)
Objective: Lymphoma is a type of cancer that starts in the immune system's lymphocytes, which fight infections. The spleen, thymus, bone marrow, lymph nodes, and other organs contain these cells. When lymphoma occurs, lymphocytes alter and proliferate uncontrollably. This study is one of the initial Iraqi efforts to investigate the serum Procalcitonin, TNF-α, IL-6, and Zinc levels in Lymphoma patients and compare the values with those of healthy controls.